Elastoplastic Invariant Relation for Deformation of Alkali-Halide Crystals; Advanced Materials Research; Vol. 1085 : Prospects of Fundamental Sciences Development (PFSD-2014) - Barannikova S. A. (2015, 2015)
Title screen